Microalgae cultivation in raceway ponds: Advances, challenges, and hydrodynamic considerations - Imane Skifa; Nicolas Chauchat; Pierre-Henri Cocquet; Yves Le Guer (EFB Bioeconomy Journal)
Microalgae cultivation in raceway ponds represents a significant advancement in the bioeconomy, offering a sustainable solution to the environmental challenges posed by industrialization and population growth. This review explores the historical development, current practices, and future potential of microalgae mass culturing, with a particular focus on the hydrodynamic considerations in raceway ponds. The cultivation process, from early-stage batch cultures to modern raceway pond systems, highlights the importance of optimizing operational parameters such as light, temperature, nutrients, pH, and salinity. The article also examines the challenges of contamination, mixing dynamics, and the effects of shear stress on microalgae growth. Recent advancements in raceway pond design, including improved agitation mechanisms and hydrodynamic models, are discussed to enhance biomass productivity and cultivation efficiency. This review identifies current methodologies, constraints, and areas requiring further research to advance the field of microalgae cultivation in open pond systems, ultimately contributing to a more sustainable bioeconomy.